The Relationship between Job Satisfaction and Good Governance in the Work Culture of Drivers within Transport Business - Abdul-Kahar Adam (New Advances in Business, Management and Economics Vol. 7, 2025)
Background: Work Culture is seen as the behaviours, attitudes, commitments and staff performance are key in advancing towards organisational objectives. Job satisfaction, on the other hand, states that both extrinsic and intrinsic factors, such as the salary increment and employees’ welfare, are paramount to the hearts of staff. Moreover, good governance is consensus-oriented, participatory, transparent, accountable, efficient and effective, responsive, inclusive and equitable, which follows the rule of law. Aims: This is theoretically basic research with conceptual studies theories, aimed at establishing the importance of work culture within organisations. This study also investigates the correlations among three variables as a model, namely Job Satisfaction, Good Governance and Work Culture. Place and Duration of Study: The study was conducted in Ghana, involving drivers from the public sector transport companies, using a designed survey questionnaire. Methodology: This was a quantitative research study. A random sample of 40 public bus drivers was interviewed, with their responses used to generate data for analysis in SmartPLS. The results indicated that all three variable constructs are valid and reliable. Results: Work Culture has a direct correlation with job satisfaction and good governance. The Cronbach Alpha for Job Satisfaction, Good Governance, and Work Culture was 0.7, 0.8, and 0.7 consecutively (Cronbach alpha value of 0.6 and above denotes there is high reliability). Conclusion: The path model indicates that the practicality of the variables is theoretically correlated and associative. This conceptual research showed that in the transport industry, especially the public sector, more attention must be paid to these three variables to achieve objectives, namely good governance, job satisfaction and work culture, to improve the human resource management practices in the public transportation industry. Future research with a large population and sample size is recommended for analysis.